Integrating Aboriginal Perspectives in Education: Perceptions of Pre-Service Teachers - Deer, Frank (Canadian Journal of Education/Revue canadienne de l'éducation, 2013)
This study explored teacher candidates’ perceptions of the potentialities and challenges associated with the integration of Aboriginal perspectives into mainstream education. Participants in this study were 2nd-year teacher candidates of a two-year teacher education programme who have completed a course on Aboriginal education. Using a qualitative approach, the principal investigator conducted interviews with teacher candidates in an effort to acquire data on pre-service teacher perceptions of and attitudes towards Aboriginal perspectives as a field of study and practice. This study found that while some participants reported a great deal of comfort in the study and delivery of Aboriginal perspectives in their respective school experiences, a significant number of participants reported apprehension. The findings of this study suggest that there are a number of variables that may lend to a positive experience for teacher candidates who are responsible for integrating Aboriginal perspectives in their respective practices.